Interaction between chromatin proteins MECP2 and ATRX is disrupted by mutations that cause inherited mental retardation. - Nan, X; Hou, J; Maclean, A; Nasir, J; Lafuente, M; Shu, X; Kriaucionis, S; Bird, A (2007)
Mutations in the human methyl-CpG-binding protein gene MECP2 cause the neurological disorder Rett syndrome and some cases of X-linked mental retardation (XLMR). We report that MeCP2 interacts with ATRX, a SWI2/SNF2 DNA helicase/ATPase that is mutated in ATRX syndrome (alpha-thalassemia/mental retardation, X-linked). MeCP2 can recruit the helicase domain of ATRX to heterochromatic foci in living mouse cells in a DNA methylation-dependent manner. Also, ATRX localization is disrupted in neurons of Mecp2-null mice. Point mutations within the methylated DNA-binding domain of MeCP2 that cause Rett syndrome or X-linked mental retardation inhibit its interaction with ATRX in vitro and its localization in vivo without affecting methyl-CpG binding. We propose that disruption of the MeCP2-ATRX interaction leads to pathological changes that contribute to mental retardation.